Sistem Informasi Berbasis WEB Pada Alumni Pondok Pesantren Nurul Haramain NWDI Narmada - Imam Fathurrahman; Muhammad Saiful; Lalu Muhammad Samsu; Nurhidayati Nurhidayati (Fakultas Teknik Universitas Hamzanwadi, 2022)
Nurul Haramain NWDI is a boarding school founded by TGKH. Djuaini Muchtar (late) in 1991, which is located in Narmada District, West Lombok Regency. Santri do not only come from the islands of Lombok or West Nusa Tenggara, but also come from various regions in Indonesia, as the years go on, more and more students enter Islamic boarding schools and of course, every year there are always students who finish their education. The lack of information about alumni that is published every year makes it difficult for students and the outside community to get information. Alumni are an important part of an educational institution, so to overcome this problem, an alumni information system is needed, to make it easier to get to know each other. Based on the results of the research that has been done by the author in the form of an information system for alumni of the Nurul Haramain Islamic Boarding School NWDI Narmada web-based, where in building this system used system development tools in the form of software used, such as data flow diagrams (DFD), PHP, which is a programming language. and My SQL for the database.